ANALISA KECENDERUNGAN DAN JENIS GAYA BELAJAR MENGGUNAKAN METODE LEARNING STYLE INVENTORY (LSI) - Sukmana, Sulaeman Hadi (LPPM Universitas Nusa Mandiri, 2017)
Analysis of the tendency of learning styles and types of learning styles aims to identify the weaknesses and advantages of a student in the process of teaching Study abroad and absorb the information given in a classroom so that teachers can improve learning achievement. The method used in this study based on the method of Learning Style Inventory introduced by David Kolb, the steps being taken are the Identification of Problems, Study litelatur, Designing Questionnaire, Validation Question, Determining Sample, Data Gathering, Analysis and Conclusions. The results showed that there were 12% (14 people) have a tendency Flavorings, 21% (23 people) a tendency Observer, 22% (24 people) a tendency Thinkers and 45% (50 people) action tendencies. The types of learning styles diverging by 39% (43 people), then asimilator by 22% (25 people) akomodator by 21% (23 people) and converges at 18% (20 people) of the total 111 students who filled out a questionnaire.